2015
DOI: 10.1001/jamainternmed.2014.5835
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness of Integrating Depression Care Management Into Medicare Home Health

Abstract: IMPORTANCE Among older home health care patients, depression is highly prevalent, is often inadequately treated, and contributes to hospitalization and other poor outcomes. Feasible and effective interventions are needed to reduce this burden of depression.OBJECTIVE To determine whether, among older Medicare Home Health recipients who screen positive for depression, patients of nurses receiving randomization to an intervention have greater improvement in depressive symptoms during 1 year than patients receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 65 publications
(140 reference statements)
0
57
0
Order By: Relevance
“…Depression severity did not differ at 3 months or 6 months in the Depression CAREPATH and control groups. 13 The 12-month measurement did demonstrate effectiveness in the Depression CAREPATH group. The researchers concluded that home health nurses can effectively integrate depression into routine practice and can clinically benefit patients with moderate to severe depression.…”
Section: Telephones Are a Valuable Technological Toolmentioning
confidence: 89%
See 3 more Smart Citations
“…Depression severity did not differ at 3 months or 6 months in the Depression CAREPATH and control groups. 13 The 12-month measurement did demonstrate effectiveness in the Depression CAREPATH group. The researchers concluded that home health nurses can effectively integrate depression into routine practice and can clinically benefit patients with moderate to severe depression.…”
Section: Telephones Are a Valuable Technological Toolmentioning
confidence: 89%
“…Depression severity was assessed using the Hamilton Scale for Depression for 306 participants. 13 Home health nursing teams at 6 nationwide home health care agencies were randomly assigned to participants who would also receive the intervention of the Depression CAREPATH and participants who would not receive the intervention. 13 Nurse teams assigned to the depression intervention were trained to manage depression during routine home visits by conducting symptom assessment, medication management, care coordination, education, and goal setting.…”
Section: Telephones Are a Valuable Technological Toolmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of the Depression CAREPATH in reducing depressive symptoms in Medicare Home Health patients has been demonstrated in a randomized trial conducted in six, geographically distinct home health agencies (Bruce et al, 2015). The study randomized teams of nurses to intervention or enhanced usual care.…”
Section: Discussionmentioning
confidence: 99%